The linguistic approach of Abu Al-Hasan Al-Mawardi in his interpretation (Al-Nukat wa Al-Ayun). - Samaah, Ass Prof. Abdul Zahra Kazem (Thi Qar Arts Journal, 2023)
We dealt in this modest research (the linguistic approach of Abu al-Hasan al-Mawardi in his interpretation: the points and eyes), and the aim of this research is to answer several questions, which are: What is meant by al-Mawardi’s approach in language? And what are the methods that he adopted in order to reach the intended meaning of the verse? And what are the sources that he referred to, and benefited from, and how did he deal with them? And we followed in this research the descriptive approach, and the study concluded with several results, one of the most important of which is: that al-Mawardi presented the opinions of linguists and interpreters of different schools of Basra, Kufa and Baghdad in a comprehensive manner, and he weighs his opinion or extracts another opinion that he adds to the opinions that he presents according to the evidence that he adopted, and in most cases he expresses it by (a probable opinion), or (it is possible for me), in addition to that, his linguistic efforts for the words were characterized by objectivity and calm dialogue, as there is no touch of bias or slander in his interpretation of anyone, and for this he occupied a distinguished position among other books of interpretation.